Critical digital literacy and the dynamics of English language learning practices: Saudi perspectives - Abdelhalim, Safaa M. (Penerbit Universiti Kebangsaan Malaysia, 2024)
The concept of literacy has evolved beyond traditional reading and writing skills, encompassing dynamic practices driven by digital sources and distributed cultures. However, empirical research suggests that despite their familiarity with web-based technologies, digital natives often lack the critical digital literacy (CDL) skills necessary for effective digital citizenship and academic contexts. The same concern applies to language learning as well. Therefore, it is crucial for language education to identify and examine the beliefs and practices related to CDL among EFL learners. This large-scale study focuses on CDL with a specific emphasis on the Arabic-speaking context, specifically targeting EFL undergraduates who are actively involved in supporting their language learning through self-study using online sources. The main aim of this study is to explore CDL practices among these students, investigate the impact of engaging in CDL practices on their language learning, and examine the correlation between CDL practices and language learning engagement. Furthermore, the study explores factors that facilitate or hinder CDL practices, considering demographic variables such as gender, academic major, and language proficiency. Using a mixed-methods approach with a descriptive cross-sectional survey design, data were collected from 387 first-year EFL undergraduates through structured and open-ended questions. The findings revealed diverse CDL practices among students, with positive perceptions of its impact on language learning. There was a positive correlation between CDL practices and English language learning engagement. Students identified several factors that mediated the development and practice of CDL skills. Significant pedagogical implications and potential directions for future research aimed at enhancing CDL among EFL learners are discussed.